Implementasi Metode Moosra dalam Seleksi Penerimaan Beasiswa Pada Perguruan Tinggi “X”di Pamekasan - Wajdy, Farid (CV. Green Publisher Indonesia, 2025)
The determination of scholarship recipients at university X in Pamekasan is a strategic process that requires objectivity, accuracy, and transparency in decision-making. The complexity of the selection process arises due to many criteria that must be considered, such as academic achievement, economic condition of students, and involvement in non-academic activities. Assessments that are still subjective have the potential to cause inaccuracies in the determination of scholarship recipients. Therefore, this study aims to implement the Multi-Objective Optimization method on the basis of Simple Ratio Analysis (MOOSRA) as a decision support system in determining scholarship recipients in a more structured and measurable manner. The MOOSRA method is used to carry out the process of normalization, weighting, and alternative ranking by considering the benefits and cost criteria simultaneously. The results of the study show that the MOOSRA method is able to produce a consistent, objective, and easy-to-understand ranking of prospective scholarship recipients by decision-makers. In addition, the application of this method can minimize the element of subjectivity and increase efficiency and fairness in the selection process. The resulting decision support system also provides convenience in data processing and systematic evaluation of alternatives. Thus, the MOOSRA method can be used as an effective and reliable alternative in supporting decision-making in determining scholarship recipients in the university environment.